The Intervention Effect Of Effleurage Technique On Children WHO Experience Constipation - Nur Hijrah Tiala; Faidana Yaumil Syifa (Sean Institute, 2024)
Background: Constipation is a common digestive problem in children, often caused by dietary factors, lack of physical activity, or emotional stress. If left untreated, constipation can lead to discomfort, abdominal pain, and complications such as fecal impaction. Various management strategies are available, including dietary modifications, increased fluid intake, and physical interventions such as abdominal massage. One of the effective non-pharmacological approaches to managing constipation is the effleurage massage technique, a gentle stroking movement that stimulates intestinal peristalsis and promotes bowel movements. Aims: This study aimed to show the effectiveness of the application of effleurage techniques in children who experience constipation.Methods: The research design used was descriptive with a case study method approach. The case study subjects in this study were two children aged 3-6 years who experienced constipation. Results: This research showed that on the first day, both respondents were unable to defecate. On the second day, both respondents still had not defecated. However, on the third day, respondent 1 was able to defecate, with stool in the form of small, solid balls, while respondent 2 also defecated, with solid and brownish feces. These results indicate that the effleurage massage therapy technique was effective in relieving constipation.Conclusion: Effleurage massage techniques on the abdomen can increase intestinal peristalsis, leading to improved bowel movements and reduced symptoms of constipation. This technique can be considered as a safe, simple, and effective non-pharmacological intervention for managing constipation in children.